MOTIVASI BELAJAR SISWA MIS I'ANATUSHIBYAN 02 PARUNG - Nurlailah Nurlailah; Rika Oktapiani; Ika (LP2M IAI Al Khairat Pamekasan, 2021)
Besides that, school is also a product where humans are educated and nurtured to become smart, productive, and qualifield human beings. The main purpose of education is to help students develop every potential that exsists in them so that they can become human beings who are balanced between their personal and social lives. The quality of student education outcomes can be determined by many factors, one of the most important is student motivation. Student motivation to learn greatly determines the success achieved by these student. Student who have high learning motivation will be able to achieve high learning achievement as well, but conversely, stuydent who have low motivation tend to get low learning achievement as well and will experience higher learning disabilities. To help increase a student’s motivation to learn, it is necessary to know the level of student motivation to learn. The phenomenon in the field shows that the level of student learning motivation is very important to know so that it can help these student to improve it, this is known after the researcher conducted interviews with supervisors at the school, according to the supervisor some students in the school had low motivation. To actively participate in teaching and learning activities in the classroom. Student motivation in this study is related to motivation, driving, change, and goals of motivation it self. The school that was taken as the research location was MI I’anatusshibyan 02 Parung. The students referred to in this study were all students of MI I’anatusshibyan 02 Parung.